Samarium-doped hydroxyapatite: An effective approach for enhancing biomineralization in dental caries management - C.P. Harini; Radha Gosala; Ramya Ramadoss (Journal of Oral Biology and Craniofacial Research)
Background: Dental caries is a widespread non-communicable disease caused by interactions among acidogenic bacteria, fermentable carbohydrates, and host factors, leading to tooth demineralization. In dentin caries, this process exposes dentinal tubules, causing sensitivity and structural degradation. Despite available agents, effective dentin remineralization remains a challenge. Recent studies highlight samarium-doped hydroxyapatite (Sm-HAp) as a potential biomaterial for promoting remineralization. Aim: To synthesize and characterize the samarium doped hydroxyapatite (Sm-HAp) as a potential agent in dentin remineralization. Materials and methods: Sm-HAp was synthesized via wet-chemical precipitation. Characterization was performed using SEM for morphology, FTIR for functional groups, and XRD for crystalline features. MTT assay evaluated for biocompatibility and in vitro mineralization analyzed on human tooth samples. Results: SEM showed flake-like, and needle-shaped crystals. XRD indicated the formation Sm doped hydroxyapatite without any additional phase, which further confirmed by FTIR. MTT assay showed >85 % cell viability, confirming high biocompatibility and also an efficient dentine mineralization was observed with Sm-HAp treatment. Conclusion: Sm-HAp demonstrates favorable structural, chemical, and biological properties, supporting its potential as a dentin remineralizing agent in dental caries management.